EFEKTIVITAS PROGRAM CSR "BRING BACK OUR BOTTLE" TERHADAP KESADARAN KONSUMEN PADA PELESTARIAN LINGKUNGAN: Survei Pada Followers @thebodyshop.impact - Putri Nabilah Hasanah (2023)
The World Economic Forum (WEF) highlighted that Indonesia accumulates 4.8 million tonnes of inadequately managed plastic waste annually. The Body Shop champions Corporate Social Responsibility (CSR), notably through environmental initiatives like the Bring Back Our Bottle program. This study aims to delve into the motivations of @thebodyshop.impact Instagram followers concerning their awareness of the Bring Back Our Bottle CSR initiative. It seeks to assess the appeal of messages from this program, evaluate the capacity of @thebodyshop.impact followers to engage with the "Bring Back Our Bottle" CSR, analyze how motivation, capability, and program appeal influence consumer awareness of environmental preservation, and evaluate the effectiveness of this CSR initiative on environmental consciousness. The research adopts the Elaboration Likelihood Model theory. It involved distributing Google Form questionnaires to 100 respondents, consumers of The Body Shop Indonesia, who participated in the Bring Back Our Bottle program. The methodology employed is quantitative and evaluative, utilizing both primary and secondary data. Purposive sampling was used for participant selection, and SPSS 26 software was used for data analysis. Descriptive statistical analysis indicates @thebodyshop.impact followers' motivation averaged 3.30, the appeal of the "Bring Back Our Bottle" program messages averaged 3.50, and their capability scored an average of 3.41. The findings reveal that respondents predominantly engage with the central route of the Elaboration Likelihood Model. Variable X exhibited an effectiveness value of 84%, and variable Y showed an effectiveness value of 82%. These results suggest that the Bring Back Our Bottle program significantly contributes to enhancing consumer awareness of environmental conservation